Strategi Pendekatan Historis Dan Pragmatis - Dyah Febiyani Nuralifia; Fahrizi Leandro Husaifah; Muhammad Yasin (Universitas Sains dan Teknologi Komputer, 2023)
Abstract, The practice of implementing education should refer to educational theory and be based on a clear philosophical foundation. In order for educational praxis to be guided by theory, an understanding of educational theory and its philosophical roots becomes important and strategic. Pragmatism believes that the truth or not of a theory depends on whether or not the theory is useful for humans in their livelihoods. This philosophy states that the truth or not of a theory depends on whether or not the theory is useful for humans in their livelihoods. Whether or not a result of thought, proposition or theory is judged according to its usefulness in life or according to the usefulness or not of that theory in human life. Pragmatism is a philosophical reaction to this phenomenon. William James defines pragmatism as